Histological examination of the small intestine in rats in experimental modeling of acute generalized peritonitis against the background of streptozotocin-induced diabetes mellitus - B.M. Verveha (Вісник медичних і біологічних досліджень, 2021)
The topicality of acute generalized peritonitis (AGP) against the background of diabetes mellitus is due to the prevalence of endocrine disease and high mortality in the altered course of the inflammatory process of the peritoneum as a result of hyperglycemia. The severity of this combined pathology caused to the progression of enteral insufficiency, which is accompanied by pronounced morphological changes in the wall of the small intestine, and is the gateway to bacterial contamination. The aim of the study – to research the morphological changes of the small intestine in the dynamics of experimental modeling of AGP against the background of streptozotocin (STZ)-induced diabetes. Materials and Methods. The experiment was performed on 48 white male rats. Diabetes mellitus in experimental animals was simulated by a single intraperitoneal injection of streptozotocin (Sigma) at the dose of 60 mg/kg, AGP was simulated by injecting of 0.5 ml of 10 % filtered fecal suspension into the abdominal cavity. The control group consisted of white rats (n=8), which were injected subcutaneously with saline 0.9 % NaCl (sodium chloride). A morphological study of the small intestine were performed on the first, third and seventh days of acute peritonitis on the background of concomitant diabetes mellitus. Results. The development of AGP on the background of hyperglycemia is characterized by the appearance of dystrophic changes in the cells of the small intestinal mucosa, the severity of which increases depending on the stage of development of peritonitis. It should be noted that on the 7th day of experimental modeling of this combined pathology revealed signs of vacuolar dystrophy of the myocytes, which indicates the development of a pathological process in all layers of intestine. The tendency to decrease the functional activity of the mucous membrane (decrease in the thickness and decrease in the height of the villi and the depth of the crypts) is observed during all stages of acute peritonitis. Dystrophic changes of the epithelium and muscular membrane, exudative inflammation and circulatory disorders create conditions for impaired peristalsis and translocation of intestinal microflora into the systemic circulation. Conclusions. The course of AGP on the background of STZ-induced diabetes is characterized by the appearance of dystrophic changes in the cells of the mucosa and muscular layer of the small intestine. Decreased functional activity of the mucous membrane of the small intestine and the progression of alterative and exudative changes in its wall lead to intestinal paresis and subsequent translocation of pathogenic microflora into the systemic circulation and abdominal cavity